OPERATIONAL AUDIT ON THE IMPLEMENTATION OF VALUE OF FAMILY BUSINESS - Rury Novita Sibulo; Haliah; Andi Kusumawati (ABM: International Journal of Administration, Business and Management, 2023)
The purpose of this study is to assess the efficiency and effectiveness of companies that apply the value of family business as internal control in the company's operational activities. The research data is processed by the Audit stage, namely, preliminary survey, review and testing of controls, detailed testing, and audit reports. This research focuses on the operational activities of PO Primadona which has two business lines, namely passenger bus services and freight forwarding. Based on the results of the author's research, it can be concluded that applying the value of family business in operational activities at PO Primadona Makassar is still not effective and efficient. The activities that have not been effective are online sales activities and the recording of cash receipts and cash disbursements, while the activities that have not been efficient are the reduction of passengers. The recommendations that the authors give to companies are, companies need to carry out regular system maintenance and use an automatic payment system, improve employee work discipline, and last but not least, provide computer training to the treasurer's department.